The Role of Photodynamic Therapy Mediated by Natural Photosensitisers in the Management of Peri-Implantitis: A Systematic Review - Aleksandra Warakomska; Jakub Fiegler-Rudol; Magdalena Kubizna; Dariusz Skaba; Rafał Wiench (Pharmaceutics)
Background: Peri-implantitis, an inflammatory condition leading to progressive bone loss around dental implants, represents a significant challenge in modern implant dentistry. Conventional mechanical debridement and adjunctive antibiotics or antiseptics often fail to fully eradicate complex biofilms and may promote antibiotic resistance. Photodynamic therapy (PDT) mediated by natural photosensitizers (e.g., curcumin, riboflavin, and 5-aminolevulinic acid) has emerged as a potential adjunctive strategy for peri-implantitis management due to its targeted antimicrobial and anti-inflammatory effects. Objectives: This systematic review aimed to evaluate the antimicrobial efficacy, clinical outcomes, and safety of PDT mediated by natural photosensitizers in the treatment of peri-implantitis and to identify optimal protocols regarding photosensitizer concentrations, light source parameters, and application techniques. Methods: Following PRISMA 2020 guidelines, databases (PubMed/Medline, Embase, Scopus, and Cochrane Library) were searched from 1 January 2015 to 3 January 2025 for English-language publications. Studies assessing naturally based PDT interventions for peri-implantitis or in vitro biofilms from diseased implant surfaces were included. Quality assessment used the Revised Cochrane Risk of Bias tool (RoB 2) for randomized controlled trials and a tailored nine-item framework for in vitro studies. Eleven studies met the inclusion criteria. Results: Despite heterogeneity in methodologies, especially regarding light wavelengths, energy densities, and photosensitizer formulations, most studies reported notable reductions in bacterial viability, biofilm mass, and clinical indices (probing depth and bleeding on probing). Curcumin and riboflavin frequently demonstrated comparable antimicrobial efficacy to standard disinfectants, while 5-aminolevulinic acid (5-ALA)-based PDT also showed promising clinical and microbiological improvements. However, complete biofilm eradication was rarely achieved. Conclusions: Natural-photosensitizer-based PDT appears to be a valuable adjunct to mechanical debridement for peri-implantitis, enhancing microbial control and clinical outcomes. Standardization of PDT protocols and further well-designed clinical trials with extended follow-up periods are warranted to confirm long-term efficacy and inform evidence-based guidelines.